Analisis Pengaruh Dana Pihak Ketiga (DPK), Non Performing Financing (NPF) dan Return On Asset (ROA) terhadap Pembiayaan di PT Bank Muamalat Indonesia Tbk - Wahyuningtyas, Ida Puspitarini; Utami, Vita Fidya (el-Jizya: Jurnal Ekonomi Islam, 2021)
ABSTRACT This study aims to determine how the influence of Third Party Funds (DPK), Non Performing Financing (NPF) and Return On Assets (ROA) on Financing at PT Bank Muamalat Indonesia Tbk Period 2016-2020. The data used in this study is secondary data, namely the quarterly Financial Statements of PT Bank Muamalat Indonesia for 2016-2020 which were obtained through the official website of PT Bank Muamalat Indonesia Tbk. Data analysis using multiple linear regression analysis techniques which previously tested the classical assumption test. Hypothesis testing is done by using t test for partial testing, F test for simultaneous testing (together) and the Coefficient of Determination (R2). During the observation period, it shows that the research data is normally distributed. Based on the classical assumption test, autocorrelation symptoms were found in the variables from the classical assumption test, so it was necessary to transform the data. The results showed that: 1) DPK had a partial positive effect on Financing at PT Bank Muamalat Indonesia Tbk, 2) NPF had no partially negative effect on Financing at PT Bank Muamalat Indonesia Tbk, and 3) ROA had no partial positive effect on Financing at PT Bank Muamalat Indonesia Tbk. PT Bank Muamalat Indonesia Tbk, 4) DPK, NPF and ROA have no effect on financing at PT Bank Muamalat Indonesia Tbk. Keywords: Third Party Funds (DPK), Non Performing Financing (NPF) and Return On Assets (ROA) and Financing.